Arthur bear’s dilemma - Gustavo Federico de Baggis (Universitat Autonoma de Barcelona. Facultat de Dret, 2016)
This paper starts from current ethical and judicial dilemma in Argentina which is originated among non-governmental animal protection organizations, state institutions and public in general, because of the possibility of moving the polar bear from Mendoza zoo to a polar bear reservation in Canada. The situation in this case is similar to many others created worldwide due to the change of paradigm as regards animal protection. They start as ethical dilemmas and then they become judicial debates about the problematic dealing of animals. This dilemma is analyzed from a common point of contact between, Arthur, the bear in captivity and two paradigmatic figures such as the slave in Rome and the abandoned child or the child in crime situations in the ancient Argentine legislation. Although there is a gap in time and space, not only the slave, in old times, but also the child, in modern times, are considered imputation objects to law, without being considered full of rights (as the animals from ancient times to the present days). This hypothesis allows us to foresee in what way the human being has been changing his judicial thought in different times and historic contexts and how now in countries such as Bolivia and Ecuador, constitutional rank has been provided to animal protection. For this, the analysis starts from the philosophical currents, from Descartes –who thinks that as animals have no soul, they do not deserve any consideration- to John Locke –who believes that cruelty to animals may have negative effects in children’s ethical evolution. Then the figures of servus romano and the abandoned child or in crime situation in the old Child-welfare Agency (“Patronato de Menores”) law in Argentina are introduced and it´s seen how in the praxis o in law, although they are temporary and spatial different, the both judicial situation is similar. The paper finishes with a brief analysis of the judiciary state of people who, because of different reasons, factual or legal, lack the will capacity without losing the judicial status of person and the possibility of fitting animals into a similar position.